2021
DOI: 10.1111/fwb.13858
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial bloom associated with a complete turnover of a Daphnia population in a warm‐temperate eutrophic lake in Eastern China

Abstract: 1. The effect of cyanobacterial blooms on aquatic ecosystems has received wide attention, yet little is known about their impacts on zooplankton genetic structure.2. For 26 months (April 2012-May 2014), we monitored zooplankton in a warmtemperate ice-free lake in Eastern China, with an emphasis on seasonal population dynamics of the cladoceran, Daphnia galeata. There was a seasonal succession in the zooplanktonic community (composed of Cladocera, Copepoda, and Rotifera).3. Genetic analysis (based on 14 microsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Interference of cyanobacteria with community structure and traits continues to attract attention as a predictor of aquatic ecosystem function (Gao et al, 2022; Ma et al, 2022). The present study revealed that both MP‐ Mic and MF‐ Mic significantly affected the morphological and life‐history responses of D .…”
Section: Discussionmentioning
confidence: 99%
“…Interference of cyanobacteria with community structure and traits continues to attract attention as a predictor of aquatic ecosystem function (Gao et al, 2022; Ma et al, 2022). The present study revealed that both MP‐ Mic and MF‐ Mic significantly affected the morphological and life‐history responses of D .…”
Section: Discussionmentioning
confidence: 99%
“…Water quality in China has declined in recent decades due to rapid urbanization and industrialization (Liu and Raven, 2010;Ma et al, 2022). Although measures have been continuously taken to control pollution, the problems of eutrophication, antibiotics, heavy metals, microbial pathogens, and other pollutants persist (Xu et al, 2014;Mekonnen and Hoekstra, 2015;Zhang et al, 2015;Zhao et al, 2018;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Deaths and illnesses including diarrhoea and liver and gastric cancers caused by the consumption of contaminated water have been reported in some areas of China over the past decade (Tao and Xin, 2014;Chen et al, 2019). Eutrophication, the major concern for freshwater ecology in China, has been reported in lakes and rivers nationwide (Wang et al, 2019a;Wang et al, 2019b;Lin et al, 2021) and algal blooms remain a common unresolved issue in some water bodies (Paerl et al, 2011;Yu et al, 2020;Ma et al, 2022). As a consequence, it is important that pollution sources are identified and efficiently tracked, and management strategies properly developed.…”
Section: Introductionmentioning
confidence: 99%